Effect of Work Life Balance on Employee Performance through Job Satisfaction as an Intervening Variable - Thalia, Shelma Najwa; Bahiroh, Eloh; Zarkasyi, Ali Imron; Amiruddin, Amiruddin; Harun, Asro bin (PT. Riset Press International, 2025)
This study's backdrop is the state of workers who are doing worse, supposedly as a result of a work-life imbalance that affects their level of job satisfaction. The purpose of this study is to evaluate and assess how work-life balance affects employee performance at PT Mitra Grafika Perdana, using job satisfaction as an intervening variable. The Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis tool, which is processed using SmartPLS 4.0 software, is utilized in this quantitative research methodology. 52 employees made up the overall sample size, which was obtained by employing the saturated sampling approach, which involves sampling the entire population. Questionnaires, observations, interviews, and documentation studies were used to gather data. The findings demonstrated that: